The influence of ante-natal phenytoin therapy on palatal fusion in rat embryo - Khaleel, Ruwaidah F.; Selman, Mohammad O.; Al-Ani, Imad Matloub Dally; Al-Salihi, Anam R. (Department of Anatomy, National University of Singapore, 2014)
Background: Antiepileptic drug (phenytoin) is extensively used by pregnant women who have seizure disorders. It is reported to produce a variety of facial defects, and considered as an important cause of nongenetic cleft palate in their offspring. Objective: To investigate the influence of administrating phenytoin to pregnant rats on the process of palatal fusion in rat embryos. Material & Method: Female pregnant rats (Rattus norvegicus) were divided into two groups: The control group (G1) and experimental group (G2). Each group consist of (30) pregnant rats. Group 2 are subdivided into two subgroups (G2A), (G2B), each group contain 15 pregnant female rats. Each rat was given a dose of 15 mg daily phenytoin was suspended in distilled water to obtain a concentration of 15mg/kg/day , and 0.1 mg/ kg that contain 3mg/rat/day was given I/P. From (E19-E16) of gestation when mothers of G2A reach (E20) of gestation cesarean section done and weighted embryos and cut the head of embryos, however when mothers of G2B reach (E21) of gestation normal delivery occur and weighted embryos and cut the head of embryos of gestation and 50 embryo from each group was used for histological preparation. Result: At embryonic day 20 (E20) and day 21 (E21), there was delay union of palatal shelves, cartilaginous structure persist and was longer Phenytoin treated group than normals. Conclusion: The present study did not demonstrate clefting of the palate in the phenytoin treated group. However, the histological study of the embryonic development of the palate and its morphogenesis has demonstrated that progression of fusion is taking place but with a delay in the midline seam disappearance.